General Concepts in Integrated Pest and Disease Management 2007
DOI: 10.1007/978-1-4020-6061-8_11
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Management Of Insect Borne Viruses By Means Of Transmission Interference As An Alternative To Pesticides

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 140 publications
0
2
0
Order By: Relevance
“…While Q performed better on TYLCV-infected tomato plants than on uninfected ones, whereas B performed better on uninfected tomato plants than on TYLCV-infected ones22. The transmission of plant viruses by insect vectors has been explored for over a century28. Several studies have shown that virus-induced plant reactions shape the behavior, physiology, and dynamics of the insect vectors, sometimes inducing changes in the insect vectors that favor virus transmission2527.…”
Section: Discussionmentioning
confidence: 99%
“…While Q performed better on TYLCV-infected tomato plants than on uninfected ones, whereas B performed better on uninfected tomato plants than on TYLCV-infected ones22. The transmission of plant viruses by insect vectors has been explored for over a century28. Several studies have shown that virus-induced plant reactions shape the behavior, physiology, and dynamics of the insect vectors, sometimes inducing changes in the insect vectors that favor virus transmission2527.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous insect vectored plant viruses are transmitted in a non-persistent or semipersistent non-circulative manner with the virus maintained only temporarily in the mouthparts or foregut of the vector without circulating through its body; however, a significant number is transmitted in a persistent circulative manner in which the viruses cross the gut epithelium and circulate through the body of the insect vector to ultimately colonize the salivary glands before being transmitted to plants during feeding 3 . In the latter case, some viruses can replicate within the vector and are called propagative for which transmission can be maintained even during the entire lifespan of the insect vector with dramatic consequences for the epidemiology and control of the virus 4 .…”
mentioning
confidence: 99%